Uncovering the genetic diversity within the Aedes notoscriptus virome and isolation of new viruses from this highly urbanised and invasive mosquito. Issue 2 (6th October 2021) - Pyke, Alyssa T; Shivas, Martin A; Darbro, Jonathan M; Onn, Michael B; Johnson, Petrina H; Crunkhorn, Andrew; Montgomery, Ivan; Burtonclay, Peter; Jansen, Cassie C; van den Hurk, Andrew F
Abstract: The Australian backyard mosquito, Aedes notoscriptus, is a highly urbanised pest species that has invaded New Zealand and the USA. Importantly, Ae. notoscriptus has been implicated as a vector of Ross River virus, a common and arthritogenic arbovirus in Australia, and is a laboratory vector of numerous other pathogenic viruses, including West Nile, yellow fever, and Zika viruses. To further explore live viruses harboured by field populations of Ae. notoscriptus and, more specifically, assess the genetic diversity of its virome, we processed 495 pools, comprising a total of 6, 674 female Ae. notoscriptus collected across fifteen suburbs in Brisbane, Australia, between January 2018 and May 2019. Nine virus isolates were recovered and characterised by metagenomic sequencing and phylogenetics. The principal viral family represented was Flaviviridae . Known viruses belonging to the genera Flavivirus, Orbivirus, Mesonivirus, and Nelorpivirus were identified together with two novel virus species, including a divergent Thogoto-like orthomyxovirus and an insect-specific flavivirus. Among these, we recovered three Stratford virus (STRV) isolates and an isolate of Wongorr virus (WGRV), which for these viral species is unprecedented for the geographical area of Brisbane. Thus, the documented geographical distribution of STRV and WGRV, both known for their respective medical and veterinary importance, has now been expanded to include this major urban centre. Phylogenies of the remaining five viruses, namely, Casuarina, Ngewotan, the novel Thogoto-like virus, and two new flavivirus species, suggested they are insect-specific viruses. None of these viruses have been previously associated with Ae. notoscriptus or been reported in Brisbane. These findings exemplify the rich genetic diversity and viral abundance within the Ae. notoscriptus virome and further highlight this species as a vector of concern with the potential to transmit viruses impacting human or animal health. Considering it is a common pest and vector in residential areas and is expanding its global distribution, ongoing surveillance, and ecological study of Ae. notoscriptus, together with mapping of its virome and phenotypic characterisation of isolated viruses, is clearly warranted. Immanently, these initiatives are essential for future understanding of both the mosquito virome and the evolution of individual viral species.